Augmented Reality in Learning: Its Impact on the Understanding of Abstract Concepts - Arimbi Pamungkas; Rahayu Soraya; Ahmad Tohir (PT. Anagata Sembagi Education, 2026)
This study investigates the effect of immersive simulation-based learning on students’ empathy development compared to video-based learning and non-technology instruction. A randomized controlled trial with a pre-test–post-test design involving three groups was employed. A total of 120 undergraduate students aged 18–25 years were randomly assigned to a virtual reality (VR) simulation group, a video-based learning group, and a control group. Empathy was measured as a latent construct consisting of cognitive and emotional dimensions, adapted from established empathy theory. Data were analyzed using repeated measures ANOVA and Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that the VR simulation group demonstrated a significantly greater increase in empathy compared to the other groups. Structural modeling further revealed that immersive simulation had a stronger positive effect on empathy than video-based learning. These findings suggest that immersive learning environments effectively support empathy development through integrated cognitive and emotional engagement